2016
DOI: 10.17546/msd.08866
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenomedullin Levels In Patients With Migraine During Naturel Attack And Attack Free Period

Abstract: The role of Calcitonin gene related peptide (CGRP) in migraine has been demonsrated. The aim of this study was to examine the role of Adrenomedullin (AM) which is a member of the calcitonin/CGRP/amylin family in migraine patients during naturel attack and attack free period.Material and Method: Twenty-six migraine patients (11 with aura, 15 without aura) and 26 healty participants were involved. Blood samples were obtained from each patient in attack and attack free period, then compared with each other and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Hence, adrenomedullin might induce migraine at possibly supraphysiological concentrations, by also activating the CGRP receptor, but the possibility of the occurrence of an attack at physiological concentrations is unclear to the best of our knowledge. A previous study in migraine patients showed lower plasma levels of adrenomedullin in the ictal and interictal phase compared to controls, suggesting an imbalance between CGRP and adrenomedullin in the migraine pathophysiology [ 101 ]. Moreover, which adrenomedullin-responsive receptors (AM 1 , AM 2 ) or the CGRP receptor mediate these migraine-like responses have yet to be elucidated [ 99 ].…”
Section: Metabotropic Receptors (G Protein-coupled Receptors)mentioning
confidence: 99%
“…Hence, adrenomedullin might induce migraine at possibly supraphysiological concentrations, by also activating the CGRP receptor, but the possibility of the occurrence of an attack at physiological concentrations is unclear to the best of our knowledge. A previous study in migraine patients showed lower plasma levels of adrenomedullin in the ictal and interictal phase compared to controls, suggesting an imbalance between CGRP and adrenomedullin in the migraine pathophysiology [ 101 ]. Moreover, which adrenomedullin-responsive receptors (AM 1 , AM 2 ) or the CGRP receptor mediate these migraine-like responses have yet to be elucidated [ 99 ].…”
Section: Metabotropic Receptors (G Protein-coupled Receptors)mentioning
confidence: 99%